Spontaneous arrangement of a tumor targeting hyaluronic acid shell on irinotecan loaded PLGA nanoparticles. (20th April 2016) - Giarra, Simona; Serri, Carla; Russo, Luisa; Zeppetelli, Stefania; De Rosa, Giuseppe; Borzacchiello, Assunta; Biondi, Marco; Ambrosio, Luigi; Mayol, Laura
Graphical abstract: Highlights: PLGA nanoparticles (NPs) were decorated with hyaluronic acid (HA) moieties. Thermal, morphological and zeta potential analyses confirmed polymer arrangement. The presence of flexible HA chains on NP surface enhances NP size stability. IRIN encapsulation efficiency was of 61.2% w/w. In vitro release kinetics can be sustained up to 7–13 days. Abstract: The arrangement of tumor targeting hyaluronic acid (HA) moieties on irinotecan (IRIN)-loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) has been directed by means of a gradient of lipophilicity between the oil and water phases of the emulsion used to produce the NPs. PLGA constitutes the NP bulk while HA is superficially exposed, with amphiphilic poloxamers acting as a bridge between PLGA and HA. Differential scanning calorimetry, zeta potential analyses and ELISA tests were employed to support the hypothesis of polymer assembly in NP formulations. The presence of flexible HA chains on NP surface enhances NP size stability over time due to an increased electrostatic repulsion between NPs and a higher degree of hydration of the device surface. IRIN in vitro release kinetics can be sustained up to 7–13 days. In vitro biologic studies indicated that HA-containing NPs were more toxic than bare PLGA NPs against CD44-overexpressing breast carcinoma cells (HS578T), therefore indicating their ability to target CD44 receptor.